Four new species of Amynthas earthworms in southeastern Vietnam (Annelida, Oligochaeta, Megascolecidae) - Nguyen, Tung T.; Tran, Binh T.t.; Lam, Dang H.; Nguyen, Anh D. (Zootaxa, 2020)
Four new earthworm species of the genus Amynthas Kinberg, 1867 are described from southeastern Vietnam, named A. longiprostaticus sp. nov., A. dorsomorrioides sp. nov., A. minhdam sp. nov., and A. ocularius sp. nov. A. longiprostaticus sp. nov. belongs to the A. minimus group of species, characterized by spermathecal pores in 5/6. It is distinguished by small body size with length 5–7 cm, and by elongate prostate glands, which extend over more than 10 segments. A. dorsomorrioides sp. nov. belongs to the A. morrisi group, characterized by holandry and spermathecal pores in 5/6/7. It is distinguished by a dorsal location of these pores, by one pair of large genital markings presetal in xvii, and by the absence of genital markings in the spermathecal region. A. minhdam sp. nov. also belongs to the A. morrisi group, and is distinguished by a pair of genital markings located medially in xviii and by the spermathecal diverticula, which have a small seminal chamber sub-divided by constrictions into 4 or 5 parts, in chain-form. A. ocularius sp. nov. belongs to the A. gracilis group by virtue of holandry and spermathecal pores in 5/6/7/8. It is distinguished by numerous small genital markings in the male region, postsetal in xviii and presetal in xix, and arranged in a peculiar fashion reminiscent of eyeglasses connected by a bridge. With these descriptions, there are now 119 species of Amynthas known in Vietnam.